Leadership strategies for effectiveness in selected secondary schools in Jamaica - Clarke, Joycelin (2004)
Examines the extent to which leadership strategies to enhance school effectiveness were employed in selected secondary schools in Jamaica. Focuses on leadership strategies as these relate to decision-making, instruction and the learning environment.